Mexe com tudo: percepção musical no movimento do frevo - Albuquerque, Janete Florencio de Queiroz (2022)
The present work aimed at understanding the fundamentals and guidelines of musical perception practices based on frevo from body movement, which can be experienced in a conservatorial context for the musical development of technical level students. As a methodological path to be followed, I chose educational action research because its main quality is the deliberate intention for changes in educational practice through pedagogical intervention, and, thus, to produce knowledge. The research field was the Pernambuco Conservatory of Music, which allowed the creation of the discipline Musical Perception and Movement for the development of research with students of the technical course, mostly adolescents. Considering that musical perception needs to be understood inter- and transdisciplinary, the theoretical starting point was the notion of body as the main mediator between the subject and the world under the eyes of Mauss, Merleau-Ponty and Le Breton. Concepts such as enation, motor and affective entrainment, in addition to the neurophysiological evidence of the neuron-mirror system, inspired the main theoretical framework of this study, the theory of embedded musical cognition, which maintains that the way in which we feel, experience, perceive and understand music is shaped from body involvement (leman et al.) Frevo, as a phenomenon of local culture, was the main basic repertoire. Data analysis revealed that from nine pedagogical principles constructed in the pedagogical intervention it was possible to know new ways of acting. Participants understood that perceiving, playing and creating music together is much richer and more meaningful, from a musical and human point of view, than the individual approach, so usual in traditional classes. It was also evident the decentralization of teaching and learning, built interactively. In proposing the activities, my role as an educator was a mediator between the knowledge to be experienced and interactions experienced with the students. In conclusion, it was understood that new forms of action focused on the experience and musical, social, affective, scientific, historical and cultural interactions experienced in the action of the body in motion, based on a repertoire of local culture such as frevo, favors the musical perception of music students at a technical level.